Circulating Thyroid Hormones and Indices of Energy and Lipid Metabolism in Normal and Hormonally Induced Oestrus Cows - Mehdi Mohebbi-Fani; Saeed Nazifi; Somayeh Bahrami; Omid Jamshidi (Journal of Basic & Applied Sciences, 2021)
In a field study, circulating thyroid hormones, their free forms and indices of energy and lipid metabolism were measured in blood samples of 16 dairy cows expressing detectable oestrus signs. The cows were divided into two equal groups according to their days in milk (DIM=53-90 and DIM=100-150). In each group, 4 cows expressed the oestrus signs normally and the others were induced by hormone injection. Serum thyroxin (T4), free thyroxin (fT4), triiodothyronine (T3), free triiodothyronine (fT3), glucose, beta-hydroxybutyrate (BHB), non-esterified fatty acids (NEFA), triglyceride (TAG), cholesterol, very low density lipoproteins (VLDL-cholesterol), low density lipoproteins (LDL-cholesterol) and high density lipoproteins (HDL-cholesterol) were investigated. Comparison of all oestrus cows (normal or induced) between DIM groups (n=8 each) revealed lower levels of T4 (P=0.027) and T3 (P=0.022), but higher concentrations of fT4 (P=0.031) and fT3 (P=0.006) in the cows with lower DIM. Higher concentrations of TAG and VLDL (P=0.021) and cholesterol (P=0.046) as well as a tendency (P=0.074) for lower levels of BHB were other remarkable findings in cows with lower DIM. In cows with DIM=53-90, the normal oestrus cows had higher levels of T3 (P=0.044) as well as tendencies (P=0.083) for higher T4 and lower fT4 compared with induced cows. In cows with DIM=100-150, however, no significant difference was observed between the normal and induced oestrus cows. In conclusion, the cows that express oestrus signs normally may have better metabolic and thyroid hormone conditions compared to those that express heat by hormone injection. With progress in DIM, however, such differences may become less evident.